2005
DOI: 10.3168/jds.s0022-0302(05)72753-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antioxidant (α-Tocopherol and Ascorbic Acid) Fortification on Light-Induced Flavor of Milk

Abstract: The effectiveness of added antioxidants against oxidation off-flavor development in light-exposed milk was evaluated using sensory and chemical analysis. Sensory testing for similarity showed no perceivable difference between control milk and milk with added (1) 0.05% alpha-tocopherol (TOC) and (2) 0.025% alpha-tocopherol and 0.025% ascorbic acid (TOC/ASC), but did demonstrate a perceivable difference when adding (3) 0.05% ascorbic acid (ASC) alone. Subsequently, sensory testing for difference showed a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 17 publications
2
17
1
3
Order By: Relevance
“…Studies have shown that tocopherols scavenge and quench various reactive oxygen species and lipid oxidation by-products, which would otherwise propagate LPO chain reactions in membranes [35]. The standard antioxidant compound α - tocopherol, the most biologically active form of vitamin E [36], is a primary antioxidant functioning by terminating free-radical chain reactions by donating hydrogen or electrons to free radicals and converting them to more stable products [37]. α - Tocopherol has a potency to induce the increase in free radical-scavenging enzyme activities [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that tocopherols scavenge and quench various reactive oxygen species and lipid oxidation by-products, which would otherwise propagate LPO chain reactions in membranes [35]. The standard antioxidant compound α - tocopherol, the most biologically active form of vitamin E [36], is a primary antioxidant functioning by terminating free-radical chain reactions by donating hydrogen or electrons to free radicals and converting them to more stable products [37]. α - Tocopherol has a potency to induce the increase in free radical-scavenging enzyme activities [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…Comparisons between the tested analytical methods and sensory results are common in research as the two methods often agree on results (Decker et al, 2010b). Significant sensory differences have been shown to agree with analytical methods reveling effects of light oxidation (van Aardt et al, 2005b). In particular the following compounds; hexanal, 2-hexanol, heptanol, 2-octenal, and 2,4-decadienal correlate with oxidation as detected by sensory methods and the TBARS analysis (Gordon et al, 2007).…”
Section: Figure 21: Stages Of Autooxidationmentioning
confidence: 99%
“…El proceso es un reacción en cadena, que inicia con la producción de radicales libres, producto de la liberación de los ácidos grasos (8) y que se ve favorecido por tres factores principales: temperatura, contacto con el aire y la luz, acompañados del tiempo de permanencia de la leche frente a estos (9).…”
Section: Calidad De La Lecheunclassified